2002
DOI: 10.1076/apab.110.1.12.904
|View full text |Cite
|
Sign up to set email alerts
|

Combined Expression of Different Hormone Genes in Single Cells of Normal Rat and Mouse Pituitary

Abstract: Cells displaying combined expression of different pituitary hormone genes (further referred to as 'multi-hormone mRNA cells') were identified in normal rat and mouse pituitary by single cell RT-PCR. These cells do not seem to produce or store all the respective hormones the mRNAs encode for. The cells are already developed at day 16 of embryonic life (E16) in the mouse. Different peptides, such as gamma3-melanocyte-stimulating hormone (gamma3-MSH) and gonadotropin-releasing hormone (GnRH), affect different sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It has been estimated that mammosomatotrophs (cells releasing both PRL and GH) are rela- mice. 23 Overall, the Aip ϩ/Ϫ mouse model greatly resembles the human phenotype reproducing a close to identical tumor phenotype, suggesting that the factors underlying Aipdeficient tumorigenesis are similar in mice and humans. 2,3,5,9 The only major difference observed between the human and mouse phenotype was the complete penetrance of pituitary tumors in mice; all heterozygous mice developed pituitary tumor(s) when aged up till 15 months (Figure 2).…”
Section: Discussionmentioning
confidence: 98%
“…It has been estimated that mammosomatotrophs (cells releasing both PRL and GH) are rela- mice. 23 Overall, the Aip ϩ/Ϫ mouse model greatly resembles the human phenotype reproducing a close to identical tumor phenotype, suggesting that the factors underlying Aipdeficient tumorigenesis are similar in mice and humans. 2,3,5,9 The only major difference observed between the human and mouse phenotype was the complete penetrance of pituitary tumors in mice; all heterozygous mice developed pituitary tumor(s) when aged up till 15 months (Figure 2).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, some GH cells become thyrosomatotropes after a thyroidectomy [19] or protracted primary hypothyroidism [33]. Consistently, recent single-cell RT-PCR studies revealed that a large pool of AP cells expressed mRNAs for multiple AP hormones [17,27,28,29,30]. The origin of polyhormonal cells remains obscure.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, the existence of a cell pool that costores and cosecretes ACTH and TSH during cold stress has been reported (9). Finally, single-cell RT-PCR has also revealed that ϳ30% of pituitary cells display mRNAs for multiple AP hormones (17,(25)(26)(27)(28) in rats, mice, and monkeys. It is remarkable that most of the cells expressing TSH-␤ mRNA (11%) actually costored it with other AP hormone mRNAs (9%), whereas cells expressing only the TSH-␤ mRNA were much less abundant (2%; see Ref.…”
mentioning
confidence: 99%